Pembelajaran Matematika Berbasis Realistik: Studi Literatur terhadap Peningkatan Pemahaman Konsep Perkalian Siswa Sekolah Dasar (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Multiplication is a basic skill in mathematics that plays a vital role as a basis for understanding more complex concepts. However, many elementary school students still find it difficult to understand this concept because the learning approach is less varied and tends to be abstract. This study aims to review the effectiveness of the Realistic Mathematics Education (RME) approach in helping elementary school students understand the concept of multiplication better. The method used is a literature study by reviewing various previous studies on the application of RME in multiplication learning. The results of the study show that the application of RME with the help of concrete media such as number bags, puzzles, elimination boards, math boards, and magic boards is consistently able to improve students' understanding of concepts. In addition, this approach also encourages active participation, increases learning motivation, and develops students' analytical skills. The RME approach has been shown to be more capable of providing a more interesting and meaningful learning experience when compared to conventional learning methods. The implications of this study indicate that the RME approach can be a recommended method in elementary school mathematics learning to build a strong foundation in understanding mathematical concepts.